Efficacy of two proposed competition-phase training programs using (HIIT vs. SIT)on improving physical and physiological performance indicators of soccer players - AIMOUCHE, Bilal; BERDI, Taha Ilias; KHAROUBI, Mohamed Fayçal (sports creativity, 2024)
The research aimed to identify the effectiveness of 4 weeks of training using (HIIT&SIT) on improving the performance indicators of soccer players in the competition stage, the experimental approach was used on an intentional sample of 16 players under the age of 17 years who were separated into two homogeneous groups, the two groups followed the (HIIT&SIT) protocols with a size of 8 sessions showed statistical differences in favor of the post-measurement for both research groups in (SJ; MAS; Vo2max; recovery capacity and anaerobic lactic capacity), The post-measurement between the two groups showed no statistical differences.